The hidden factors behind knowledge concealment: a review-based framework - Osman, Suhaila; Hussin, Norhayati; Shahibi, Mohd Sazili (UiTM Cawangan Johor, 2025)
Organizational knowledge management fosters innovation, decision-making, continuous learning, and competitiveness. This can be readily accomplished in an organization through employee knowledge sharing. Yet, not sharing with others and concealing knowledge among employees in an organization has emerged as a significant impediment in organizations as it could prohibit the organization's ongoing growth and survival. Knowledge concealment is a compelling idea that has clear detrimental repercussions on organizations, as it stifles creativity and obstructs teamwork and collaboration, impacting organizational performance. This paper explores the hidden factors of knowledge concealment: internal competition, lack of rewards in knowledge sharing, psychological entitlement, leadership, and moral disengagement. Comprehensive studies have methodically scrutinized the different factors that lead to knowledge concealment. However, they are insufficient, as many studies have focused on the consequences, resulting in a lack of interest in investigating the factors. This research addresses the gap by examining the numerous factors that influence the existence of knowledge concealment in organizations through the literature review or survey approach. The findings of the literature review or existing research indicate that these factors have consistently demonstrated strong associations with knowledge concealment in previous studies. In addition, this study introduces a fresh conceptual framework that analyzes the hidden factors of knowledge concealment, hence offering opportunities for future research by other academics. Keywords: Hidden factors, knowledge concealment (KC), knowledge hiding (KH), knowledge management (KM), knowledge sharing (KS).